Application of tDCS in children with cerebral palsy: A mini review - Tang, Lin; Wu, Yuwei; Ma, Jiayin; Lu, Yan; Wang, Ling; Shan, Chunlei (Frontiers in Pediatrics, 2022)
Cerebral palsy (CP) refers to a group of diseases characterized by persistent central dyskinesia, postural development disorder and activity limitation syndromes caused by nonprogressive brain injury in the developing fetus or infant, which is often accompanied by sensory, cognitive and attention disorders. The routine rehabilitation methods for children with CP mainly include physical therapy, occupational therapy, speech therapy and other methods. In recent years, noninvasive brain stimulation (NIBS), as a relatively new intervention method, has been widely used because of its potential to regulate cortical excitability and plasticity. Transcranial direct current stimulation (tDCS) is an NIBS technique that is easier and more convenient to perform. It does not require patients to remain stationary for a long time or have a significant impact on treatment results due to children's frequent activities. Compared with other NIBS techniques, tDCS has greater flexibility and no strict restrictions on patients’ activities; it also helps the therapist conduct occupational therapy or speech therapy while a child receives tDCS, which markedly reduces the treatment time and avoids burnout due to a long treatment duration. Thus, tDCS is a better and more convenient intervention for CP children and warrants further exploration. Accordingly, this article reviews tDCS application in children with CP and discusses tDCS application prospects for such children to promote its expansion in clinical practice.